Cumulative Effects of Exposure to Violence on Post-Traumatic Stress in Palestinian and Israeli Youth - Dubow, Eric F. (2012)
OBJECTIVE: We examine cumulative and prospective effects of exposure to conflict and violence across four contexts (ethnic-political, community, family, school) on post-traumatic stress (PTS) symptoms in Palestinian and Israeli youth. METHOD: Interviews were conducted with 600 Palestinian and 901 Israeli (Jewish and Arab) children (ages 8, 11, and 14) and their parents once a year for three consecutive years. RESULTS: Palestinian children, males, and older youth were generally at greatest risk for exposure to conflict/violence across contexts. Regression analysis found unique effects of exposure to ethnic-political (Palestinian sample), school (Palestinian and Israeli Jewish samples), and family conflict/violence (Israeli Arab sample) during the first two years on PTS symptoms in year 3, controlling for prior PTS symptoms. Cumulative exposure to violence in more contexts during the first two years predicted higher subsequent PTS symptoms than did exposure to violence in fewer contexts, and this was true regardless of the youth’s level of prior PTS symptoms. CONCLUSIONS: These results highlight the risk that ongoing exposure to violence across multiple contexts in the social ecology poses for the mental health of children in contexts of ethnic-political violence. Researchers and mental health professionals working with war-exposed youth in a given cultural context must assess both war- and non-war-related stressors affecting youth. Based on this assessment, interventions may not be limited to individual-based, war-trauma-focused approaches, but also may include school-based, community-based, and family-level interventions.